Intermolecular copigmentation between five common 3-O-monoglucosidic anthocyanins and three phenolics in red wine model solutions: The influence of substituent pattern of anthocyanin B ring - Zhao, Xu; Ding, Bo-Wen; Qin, Jia-Wei; He, Fei; Duan, Chang-Qing (Food chemistry, 2020)
•Copigmentation between 5 anthocyanins and 3 phenolic copigments were studied.•Chromatic, thermodynamic and theoretical methods were used.•Substituent pattern of anthocyanin B ring had great influence on copigmentation.•Diverse π-π stacking modes were observed through theoretical calculation. In this study, intermolecular copigmentation between five primary wine monoglucosidic anthocyanins (cyanidin-3-O-glucoside, peonidin-3-O-glucoside, delphinidin-3-O-glucoside, petunidin-3-O-glucoside, and malvidin-3-O-glucoside) and three common wine phenolics (gallic acid, (−)-epicatechin, and quercetin-3-O-glucoside) were investigated through experimental and theoretical methods, and the influence of substituent pattern of anthocyanin B ring was studied emphatically. Chromatic and thermodynamic analysis showed there were great differences among these different pigment-copigment systems. Spatial conformations of the 15 copigmentation complexes were obtained through theoretical calculation, and diverse π-π stacking modes were observed. These results indicated that the substituent pattern of anthocyanin B ring had significant impact on its affinity to copigments, and more, the structures of pigments and copigments determined the color expression and stability of copigmentation together.